Palliative Care Pada Skizofrenia : A Literatur Review - Mamnuah, M; Trihidayati, Noorwahyu (Universitas Muhammadiyah Surakarta, 2022)
Palliative care is very important for tackling the disease, symptom management and reduction. In addition, it can also improve quality of life and reduce the risk of suicide in patients with schizophrenia. With support and attention, palliative care can be carried out with curative treatment. The purpose of this literature is to determine the use of palliative care services in schizophrenic patients. The methiod of this literature review uses 4 steps, namely (1) determining standards, (2) determining sources of information, (3) selecting literature and (4) collecting data. The search was carried out on Pubmed, Science Direct and Google scholar. Keys “Palliative care” [Mesh] AND “Spectrum of schizophrenia” OR “Psychotic disorders” [Mesh] which can be accessed in full text, free of charge and in English and has the last 5 years of publications. The results is there were 6 articles that matched the inclusion criteria and topics. From 6 articles, it was found that several obstacles in using palliative care in schizophrenia were caused by individual factors consisting of the effects of symptoms that had an impact on communication, trust, awareness, social factors such as stigma. , social support and decision making and health care factors including perceived benefits of care, multidisciplinary approach and health system factors. The conclussion of this is that barriers to families and patients in using palliative care are; individual factors, social factors, health service factors and health system factors.